# a2+bc+ab+ac =?A. (a + b) (a + c)B. (a + b) (b + c)C. (b + c) (c + a)D. a(a + b + c)

a2+bc+ab+ac = a2+ab + bc + ac

Rearranging the terms and taking a and c as common respectively.

= a(a + b) + c(a + b)

= (a + c)(a + b).

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Quiz | Important Questions on Factorisation35 mins
Algebraic Identities - Mark your Weak Areas41 mins
Quiz | Questions on Factorization41 mins
NCERT | Factorisation Problems38 mins
Champ Quiz | Division of Polynomials33 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

2x2 + 5x + 3=?

RS Aggarwal - Mathematics

ab – a – b + 1= ?

RS Aggarwal - Mathematics

40 + 3x – x2=?

RS Aggarwal - Mathematics

10p2 + 11p + 3 = ?

RS Aggarwal - Mathematics

7x2 - 19x - 6 = ?

RS Aggarwal - Mathematics

12m2 – 27 =?

RS Aggarwal - Mathematics

2 – 50x2=?

RS Aggarwal - Mathematics